SAVINGS PATTERNS AMONG Gen Z YOUTHS - Kasim, Arena Che (International Journal of Psychosocial Rehabilitation, 2020)
Savings and assets are among the earliest preparations in financial management that need to be taken into account in order to ensure a better and more organised life in the future. Failure to plan and manage finances is one of the reasons young people are likely to go bankrupt. Today’s youth, known as Gen Z is the most vulnerable group to this problem. This paper discusses the findings of a study on savings patterns among Gen Z youths. The study was conducted through a distributed questionnaire on 761 selected respondents between the ages of 15and23based on a stratified random sampling method in five identified zones in Malaysia. The results of the study were analysed using SPSS Version 22.0. The findings show that there is awareness among Gen Z to have their savings, especially at banks with 364 respondents (49.34%), Tabung Haji (201 respondents, 26.41%), cash savings (336 respondents, 44.15%), and gold savings (23 respondents, 0.13%). However, the percentage can still be improved and proactive steps need to be taken to encourage them to have savings based on their capabilities. Implications of the study indicate that parents are the closest and most important persons in providing awareness, education, and emphasis on the importance of savings and assets to these Gen Z youths.